3D clusters of somatic mutations in cancer reveal numerous rare mutations as functional targets. Issue 1 (December 2017) - Gao, Jianjiong; Chang, Matthew; Johnsen, Hannah; Gao, Sizhi; Sylvester, Brooke; Sumer, Selcuk; Zhang, Hongxin; Solit, David; Taylor, Barry; Schultz, Nikolaus; Sander, Chris
Abstract Many mutations in cancer are of unknown functional significance. Standard methods use statistically significant recurrence of mutations in tumor samples as an indicator of functional impact. We extend such analyses into the long tail of rare mutations by considering recurrence of mutations in clusters of spatially close residues in protein structures. Analyzing 10, 000 tumor exomes, we identify more than 3000 rarely mutated residues in proteins as potentially functional and experimentally validate several in RAC1 and MAP2K1. These potential driver mutations (web resources: 3dhotspots.org and cBioPortal.org) can extend the scope of genomically informed clinical trials and of personalized choice of therapy.